Online treatments for depression : a radomised controlled trial on an adult student population - Richards, Derek (Trinity College (Dublin, Ireland). School of Psychology, 2010)
Background: Depression is a serious and growing mental health concern with associated economic, social and personal costs. Depression can be effectively treated, however, only a small percentage of those who suffer, receive treatment. Online- delivered treatments may increase access and help remove some of the barriers that impede help-seeking thereby closing the gap between demand and supply. Online psychosocial treatments for a variety of disorders, including depression, have demonstrated clinical efficacy. For example, based on research, NICE have recommended Beating the Blues™ in the treatment of mild to moderate depression. In addition to efficacy, Marks et al. (2007) point out in their worldwide review of computer-aided therapy; “more needs to be known about the best type, duration and site of human support for users.” (P.222) It is important therefore to learn more about the role that therapist support plays in the delivery of online interventions.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin